Determinan “Picky Eater” (Pilih-Pilih Makanan) Pada Anak Usia 1-3 Tahun (Studi Di Wilayah Kerja Puskesmas Jabon Sidoarjo) - Niken Kusumawardhani, Windhu Purnomo, Rachmat Hargono, Siti Nurul Hidayati, Martono Tri Utomo, Sri A (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2013)
Picky eater is one of the important issues in child growth that have to be concerned by parents and health practitioners, due to the negative effect of imbalance increasing of weight, important nutrition defeciency, also lack of variation of food consumptions. If this issue does not immediately treated it can cause a long term effect of an unhealthy or slow development and growth in children. Sample of population used in this research are all children aged 1-3 years old in Posyandu of Puskesmas Jabon in March until May 2013. The type of this study was an analytic with case control design study. The total of sample was 106 children devided in case (n=53) and control groups (n=53) and using Multiple Logistic Regression Test. The outcome of this research are showing all illness that have been suffered by all children in last 3 months, lack of interaction between mother and children, parents selective food behavior, not given enough exclusive breastfed for 6 months, given weaning food less than or more than 6 months, children is raised by people other than parents, socio-cultural dietetic view, unmatching frequencies between consumption and age, improper mealtimes, and improper feeding techniques are all crucial in affeting selective eating disorder in children aged 1-3 years in area of work of Puskesmas Jabon Sidoarjo in 2013.